1996–2018年の沖縄島周辺におけるザトウクジラの漂着および混獲 - 岡部, 晴菜; 小林, 希実; 東, 直人; 徳武, 浩司; 宮原, 弘和; 内田, 詮三; Okabe, Haruna; Kobayashi, Nozomi; Higashi, Naoto; Tokutake, Koji; Miyahara, Hirokazu; Uchida, Senzo (Ryukyu University Museum, Fujukan, 2019)
ザトウクジラ(Megaptera novaeangliae)は冬季に低緯度海域へ繁殖回遊することが知られており,特に沖縄島周辺海域では,12月から4月にかけて本種の来遊が確認される.これに伴い,同時期の沖縄島周辺では,本種が死亡した状態で海浜等に打ち上げられる「漂着」や沿岸に設置された定置網による「混獲」が時折確認される.本稿では,1996年から2018年までに確認された沖縄島周辺におけるザトウクジラの漂着及び混獲について報告する.過去22年間の調査で,本種の漂着が7例,混獲(読谷村定置網)が5例,計12例が確認された.全漂着及び混獲は1月上旬から4月上旬の間に確認され,特に本種の来遊盛期とされる2月中旬から下旬に増加する傾向にあった.漂着については,1996年から2014年までの19年間で3件のみの確認であったが,2015年以降は毎年確認されるようになり,近年,漂着頻度が増加傾向にあることが伺えた.また,漂着した全個体は体長3.6–10.3m,推定年齢0–-6歳の未成熟個体であり,他海域と同様に未成熟個体の漂着数が成熟個体よりも多い傾向にあった.定置網による混獲は,全5頭であったが,いずれも１週間以内に自力もしくは介助を得て網外へ脱出した.本種の尾鰭腹面の模様と形状を自然標識とする個体識別法にて,混獲個体の尾鰭写真と混獲以降に沖縄周辺で確認された1563個体分の写真を照合したところ,5個体のうち3個体が混獲の翌年以降も沖縄島周辺へ再来遊していることが確認され,その生存が確認された. Humpback whales (Megaptera novaeangliae) are known to migrate to lower latitudes for breeding in winter including in waters around Okinawa Island between December and April. Around the same period of time, dead strandings and “bycatch” of humpback whales that are caught accidentally in fixed nets placed in coastal waters are also occasionally observed around Okinawa Island. In this paper, we report on humpback whale strandings and bycatches confirmed around Okinawa Island between 1996 and 2018. A total of 12 cases consisting of 7 strandings and 5 bycatches (in a fixed net placed in the coastal waters of Yomitan-son) were recorded during the approximately 22-year study period. All the strandings and bycatches took place between early January and early April, and their occurrence increased in the peak season for the arrival of humpback whales into Okinawan waters between the middle and the end of February. Only three dead strandings of humpback whales were recorded between 1996 and 2014, whereas one dead stranding each has been observed for 4 consecutive years since 2015; the frequency of the strandings seems to be increasing in recent years. All the stranded humpback whales were 3.6–10.3 meters in length and estimated to be 0–6 years old; therefore, they were considered sexually immature. These results indicate that the number of strandings of immature whales is larger ...